Analysis Of Proteins Extracted From The Leaves Of Piper Sarmentosum - Shim , Siang yian (2010)

(untitled)
A gel based proteomic method has been developed for the leaf tissues of P. sarmentosum. A suitable protein extraction method termed as total protein extraction followed by trichloroacetic acid (TCA)/acetone precipitation was applied and has been shown to produce good leaf tissue extract that was compatible with 2-DE separation. The protein profiling of leaf tissues of P. sarmentosum showed a total of 242 protein spots and from which 283 proteins were identified by LCMS/MS analysis. Most of these identified proteins were involved in metabolism (including photosynthesis), protein destination and storage, energy and transport, and defense and stress related protein.